(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Possibility to increase load-carrying capacity of arch-type timber roof of multifunctional public building with the span equal to 60 m was analysed. Three-hinged segment arches with the rectangular glued cross-sections are considered as the main load-carrying structures in the transversal direction. Freely supported purlins with the massive rectangular cross-sections are considered as the main load-carrying structures in the longitudinal direction. The dependences between height of the arches, it bays and distances between the bracing members strengthening top and bottom zone of the arches cross-sections so as relative materials consumption and specific load-carrying capacity of the arches were obtained as the second power polynomial equations. Height of the arches and it bay changes within the limits from 10 to 30 and from 2 to 9 m, correspondingly. The distances between the bracing members strengthening top and bottom zone of the arches changes within the limits from 2 till 10 and from 4 till 16 m, correspondingly. The arch-type timber roof was considered under the action of the load combination which include structural dead weight, drifted and undrifted snow loads and wind loads. The relative materials consumption of the arches was determined as a relation between the dead weight of the arch to it span and changes within the limits from 24 till 114 kg/m. Glued and solid timber with strength classes GL24h and C24 are considered as materials of arches and purlins, correspondingly. The specific load-carrying capacity of the arches was determined as a relation between load –carrying capacity of the arche and volume of structural materials. Specific load-carrying capacity of the arches changes within the limits from 0.23 till 0.83 kN/m/t in the case, if purlins are taken into account. It was shown, that the rational from the point of view of materials consumption and specific load-carrying capacity height of the arche, it bays so as the distances between the bracing members strengthening top and bottom zone of the arches are equal to 15, 7.5, 5 and 15 m, correspondingly. Corresponding values of relative materials consumption and specific load-carrying capacity are equal to 24 and 0.23 kN/m/t. The depth and width of the arche cross-section were equal to 1617 and 318 mm, correspondingly. It was shown, that strengthening of the arches cross-section by the steel bars of strength class B500 and carbon fibre reinforced plastic tape Sika Crbo Dur S512 enables to increase load-carrying capacity of the arche by 10.20 and 9.48%, correspondingly. But common use of the steel bars together with the carbon fibre reinforced plastic tapes enables to increase load-carrying capacity of the arche by 18.89%.